Magnetic Janus nanorods for efficient capture, separation and elimination of bacteria. Issue 6 (13th January 2017) - Chang, Zhimin; Wang, Zheng; Lu, Mengmeng; Li, Mingqiang; Li, Li; Zhang, Yi; Shao, Dan; Dong, Wenfei
Abstract : Magnetic Janus mesoporous silica nanoparticles with CTAB-loading and amino-functionalization were prepared for efficient capture, separation and elimination of bacteria. Abstract : Magnetic Janus mesoporous silica nanoparticles (MSNs) with CTAB-loading and amino-functionalization were prepared through a one-pot synthesis strategy. Janus MSNs exhibit outstanding bacterial capture and separation performance, enabling the highly efficient elimination of both Gram-negative Escherichia coli and Gram-positive Staphylococcus aureus, illustrating their application potential in biomedicine.